Digital Parenting: Bagaimana Mencegah Kecanduan Gadget Pada Anak - Ahmad Sudi Pratikno; Sumantri Sumantri (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
As a big country, Indonesia should be able to foster the youth, especially in shaping good behavior (character). Good behavior comes from good parenting. However, the current level of adoption of gadgets is increasingly worrying, subsequently concrete steps are needed to implement parenting in the digital age in order to avoid gadget addiction of children and good attitude and mental shape are formed within the child. Some efforts that can be done are by utilizing the features provided by digital companies and the iOS and Android operating systems, implementing classical conditioning, as well as making agreements between children and parents regarding the duration of gadget usage.